The Royal Courts of Equity in England in the 16-17 centuries. - I. Strizhakov (Правоприменение, 2017)
УДК 340.15The subject of research are the courts of England in 16-17 centuries.The purpose of article is to answer the question which courts must be included to a number of "courts of equity".Methodology. Historical analysis of the scientific literature, of the English legislation and judicial practice of the 16-17 centuries.Results. The priority for the Court of Star Chamber was to protect the interests of Royal power and not the rights of people. Moreover, this court did not seek to bridge the gaps of common law. In this regard, his reference to the number of “courts of equity” is incorrect.Star Chamber had a close relationship with the Privy Council. There were no clear boundaries between them during the XVI century. The Star Chamber was the emergency Committee of the Privy CouncilThe purpose of the Court of Requests was to ease social tensions, to create the impression of caring filed emanating from the monarch and the nobility.Despite the fact that the Court of the Requests was conceived as "a court for poor people", it became popular wealthy people under the rule Henry VIII.The Court of High Commission was a court focused on the strengthening of Royal power. In its activities it has been focused on improving the rights of the Kingdom.The Court of Exchequer provided judicial protection for some types of transactions that are not recognized by the common law. In this it is similar to the Chancery Court. Initially, the Court of the Exchequer has been focused on protecting the interests of the crown. Therefore, the function to eliminate the gaps of the common law could not be implemented in full.The Chancery Court, unlike the special courts were required to consider complaints coming from citizens about the inability to get a fair trial.Conclusions. The criteria for judicial institutions to be considered as “courts of equity” are: the purpose of the establishment of the court was to fill gaps in the common law; interference with the jurisdiction of other courts, in fact, has been focused on the eradication the deficiencies of the common law; the court of equity was not supposed to apply a legal fiction in their practice; specialization in civil cases. The number of “courts of equity” may be assigned only by the Chancery Court.